2016
DOI: 10.1021/acs.orglett.6b03257
|View full text |Cite
|
Sign up to set email alerts
|

Procedure for the Synthesis of Polysubstituted Carbazoles from 3-Vinyl Indoles

Abstract: A simple Brønsted acid catalyzed tandem reaction, including intermolecular nucleophilic addition, substitution and intramolecular cyclization, in a one-pot manner is described. Thirty two 2-indolyl substituted carbazoles are generated in good to excellent yields. Based on this tandem reaction strategy, the poly(1,4-carbazole) is prepared for the first time. Preliminary studies indicate that the poly(1,4-carbazole) has good thermostability and optical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…We found that this reaction could take place in the absence of phosphoric acid, which increased the difficulty to control the stereoselectivity. 14 Consequently, we turned our attention toward finding other highly efficient catalysts. According to Hosomi's work, CaCl 2 was a suitable catalyst for the aldol reaction of silyl enolates and arylgloxals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that this reaction could take place in the absence of phosphoric acid, which increased the difficulty to control the stereoselectivity. 14 Consequently, we turned our attention toward finding other highly efficient catalysts. According to Hosomi's work, CaCl 2 was a suitable catalyst for the aldol reaction of silyl enolates and arylgloxals.…”
mentioning
confidence: 99%
“…Encouraged by the preliminary experimental results, chiral phosphoric acids 3b – g were screened in this reaction; however, better results were not obtained (Table , entries 2–7). We found that this reaction could take place in the absence of phosphoric acid, which increased the difficulty to control the stereoselectivity . Consequently, we turned our attention toward finding other highly efficient catalysts.…”
mentioning
confidence: 99%
“…On the basis of the above results and the previously reported reactions, ,, a plausible reaction mechanism was relationally proposed in Scheme . In the first step, the Michael addition of 1-methylindole to 3-phenacylideneoxindole resulted in the major Michael adduct 7 and minor isomer 8 , which were gradually released to the starting material in lower concentrations by the acid catalyzed retro-Michael addition reaction.…”
Section: Resultsmentioning
confidence: 55%
“…In recent years, 3-vinylindoles have emerged as a kind of versatile chemical synthon in many asymmetric transformations, which is due to their chemical diversity through modifying the terminal alkene at the C3 position of an indole . Among them, 3-vinylindoles could participate in enantioselective addition reactions as electrophilic acceptors but, to a large extent, remained underdeveloped .…”
Section: Introductionmentioning
confidence: 99%